PENCEGAHAN ANEMIA PADA REMAJA DI INDRAMAYU - Nuraeni, Tating (Abdi Wiralodra : Jurnal Pengabdian Kepada Masyarakat, 2019)
The purpose of this activity is to provide comprehensive understanding, especially for junior high school students in Cantigi Subdistrict, Indramayu Regency about anemia in adolescents. Activities are carried out with a lecture and discussion approach to the first class VII, VIII, VIII schools. The results of this activity are the enthusiasm of participants who increasingly understand about anemia. and it is highly recommended to take Fe tablets and consume lots of foods containing iron and protein to facilitate the blood circulation system. By detecting it early so as not to disturb the reproductive system in adolescents.